Fungal and mycotoxigenic burden from feed applied in Portuguese aquaculture - Viegas, Carla (2018)
Aquaculture is one of the most important animal husbandry systems, allowing a regular growth of 1% per year in the last three decades worlwide. As in other animal production, feed safety is an essential factor to assure the productivity of those aquatic activities. The aim of this study was to assess fungal and mycotoxigenic burden in seven different feeds, four filters from aquaculture recirculation tanks and seven water samples from the same tanks.